Validation of a Self-Report Clinical Decision-Making Tool Using Rasch Analysis. Issue 3 (September 2018) - Macauley, Kelly; Brudvig, Tracy; Barry, Amanda; Lufkin, Olivia; McEnroy, Kevin; Milinazzo, Andrew
Abstract : Introduction: No objective tools exist that assess the level and progression of clinical decision-making (CDM) skills in Doctor of Physical Therapy (DPT) students. Tools in other health professions exist but are not applicable or transferable to DPT education. The purpose of the current study is to validate an objective tool to assess DPT students' perceptions of their CDM skills across a curriculum. Methods: This is a cross-sectional, observational design study, using a convenience sample of DPT students enrolled in a DPT program. Four phases of data collection, representing four iterations of the CDM tool, are included. A self-report tool assessing CDM using a Likert scale was sent to the participants through email. Data were analyzed using Rasch analysis after each phase of data collection, which led to survey revisions and further data collection. Results: The tool demonstrated high internal consistency throughout the four phases of data collection. The tool measures one construct, CDM. The Likert scale levels discriminated well between the different ability levels on all items. The scores on the CDM tool provided known groups validation of the tool. The tool has a ceiling effect, floor effect, and is unable to differentiate CDM skills for DPT graduates who have been practicing for >1 year. Discussion: Clinical decision making is a complex, highly individualized construct. This CDM tool distinguishes the students' perceived level of CDM ability across the different class years of a DPT curriculum. The sample was one of convenience. Further research increasing the heterogeneity of the sample will assist with increasing the generalizability of the tool. Abstract : Supplemental Digital Content is Available in the Text.